2015
DOI: 10.1073/pnas.1403322112
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome extensions deliver the Arabidopsis SDP1 lipase to oil bodies

Abstract: Lipid droplets/oil bodies (OBs) are lipid-storage organelles that play a crucial role as an energy resource in a variety of eukaryotic cells. Lipid stores are mobilized in the case of food deprivation or high energy demands-for example, during certain developmental processes in animals and plants. OB degradation is achieved by lipases that hydrolyze triacylglycerols (TAGs) into free fatty acids and glycerol. In the model plant Arabidopsis thaliana, Sugar-Dependent 1 (SDP1) was identified as the major TAG lipas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
135
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 34 publications
3
135
0
Order By: Relevance
“…No such docking signals in oleosins or perilipins on mammalian LDs are known. Naturally, lipase must bind to LDs for lipolysis, as shown in Arabidopsis seed (Thazar-Poulot et al, 2015). Phosphorylated perilipin interacts with lipase via a lipase moderator, a/b hydrolase domain-containing protein5, and binds to mitochondria via its C-terminal peptide; motifs in perilipin for these interactions are unknown (Wang et al, 2011).…”
Section: Oleosin Transcripts Are Present In Fruit Mesocarp Of Avocadomentioning
confidence: 99%
“…No such docking signals in oleosins or perilipins on mammalian LDs are known. Naturally, lipase must bind to LDs for lipolysis, as shown in Arabidopsis seed (Thazar-Poulot et al, 2015). Phosphorylated perilipin interacts with lipase via a lipase moderator, a/b hydrolase domain-containing protein5, and binds to mitochondria via its C-terminal peptide; motifs in perilipin for these interactions are unknown (Wang et al, 2011).…”
Section: Oleosin Transcripts Are Present In Fruit Mesocarp Of Avocadomentioning
confidence: 99%
“…Peroxules can mediate interorganellar contacts, such as among peroxisomes and ER (Sinclair et al, 2009), oil bodies (Thazar-Poulot et al, 2015), mitochondria (Jaipargas et al, 2016), and chloroplasts (Gao et al, 2016). Moreover, peroxules can respond to environmental signals.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Finally, live cell imaging of peroxisomes in mammals and plants revealed that peroxisomes can form tubular membrane protrusions, which vividly extend and retract, and are thought to mediate interactions with other peroxisomes and organelles. Very recently, peroxisomal membrane extensions were reported to mediate contact with oil bodies (see Section Lipid Droplets) in the model plant Arabidopsis thaliana and to deliver a membrane-bound lipase, required for lipid mobilization during seedling establishment (Thazar-Poulot et al, 2015). Membrane protrusions may also be involved in the transfer of membrane lipids.…”
Section: Interplay Between Peroxisomes and Mitochondriamentioning
confidence: 99%
“…RAB18 presumably binds to droplets from the cytosol through its isoprenoid modification, similar to other Rab proteins. Finally, a triacylglycerol (TAG) lipase in Arabidopsis thaliana, SDP1, can transit to droplets from peroxisomes via a retromer complex (previously known to transport proteins from endosomes to the trans-Golgi network) during seed development (Thazar-Poulot et al, 2015). Bridges between the ER and droplets should allow transfer of phospholipid and neutral lipids between these two compartments.…”
Section: Er To Droplet Traffickingmentioning
confidence: 99%
See 1 more Smart Citation